PENINJAUAN ULANG PENGGUNAAN ADS-B TERHADAP PELAYANAN LALU LINTAS PENERBANGAN DI PERUM LPPNPI KANTOR CABANG MEDAN - Fahmi, Riza Rahmaddian; Amir, Elfi (Jurnal Penelitian, 2024)
Kualanamu Medan Airport provides air traffic services, there are aerodome control services, approach control services, and area control services by using existing technological developments. One of them is flight navigation equipment that used to be conventional, such as Radar, now starting to switch to Automatic Dependent Surveillance-Broadcast (ADS-B). Based on the results of existing observations, it is known that the ADS-B equipment at Perum LPPNPI Medan Airport has not yet been certified and standardized, so there are still frequent differences in the information provided between the ADS-B and the Radar. The research method used is a qualitative method with a descriptive approach. While the technique of collecting data by mean of interviews and observation. The advice that the author can give is a short-term solution in the form of reviewing the use of the ADS-B tool at Perum LPPNPI Medan because there is no such certification and a long-term solution, namely updating the Air Traffic Control System (ATC System) in Perum LPPNPI Medan to help use the ADS-B tool in the future.